A global correlation of the step-wise consolidated crust-stripped gravity ﬁeld quantities with the topography, bathymetry, and the CRUST 2.0 Moho boundary - TENZER, Robert; HAMAYUN, K; VAJDA, Peter (Contributions to Geophysics and Geodesy, 2009)
We investigate globally the correlation of the step-wise consolidated crust- stripped gravity ﬁeld quantities with the topography, bathymetry, and the Moho bound- ary. Global correlations are quantiﬁed in terms of Pearson’s correlation coeﬃcient. The elevation and bathymetry data from the ETOPO5 are used to estimate the correlation of the gravity ﬁeld quantities with the topography and bathymetry. The 2×2 arc-deg discrete data of the Moho depth from the global crustal model CRUST 2.0 are used to estimate the correlation of the gravity ﬁeld quantities with the Moho boundary. The results reveal that the topographically corrected gravity ﬁeld quantities have the highest absolute correlation with the topography. The negative correlation of the topographically corrected gravity disturbances with the topography over the continents reaches –0.97. The ocean, ice and sediment density contrasts stripped and topographically corrected gravity ﬁeld quantities have the highest correlation with the bathymetry (ocean bottom relief ). The correlation of the ocean, ice and sediment density contrasts stripped and topographically corrected gravity disturbances over the oceans reaches 0.93. The consolidated crust-stripped grav- ity ﬁeld quantities have the highest absolute correlation with the Moho boundary. In particular, the global correlation of the consolidated crust-stripped gravity disturbances with the Moho boundary is found to be –0.92. Among all the investigated gravity ﬁeld quantities, the consolidated crust-stripped gravity disturbances are thus the best suited for a reﬁnement of the Moho density interface by means of the gravimetric modeling or inversion.